Morphology controlling of silver by plasma engineering for electrocatalytic carbon dioxide reduction - Yu, Qing (2020)
Morphology is crucial for catalyst performance, particularly in carbon dioxide (CO2) electroreduction because its selectivity over water reduction is very sensitive to catalyst surface morphology. Leveraging plasma engineering, we have developed a facile plasma activation process to control the morphology of silver electrocatalyst for CO2 reduction reaction (CO2RR). By controlling the oxygen plasma conditions, we could tune the silver morphology; and hence optimize the catalytic activity to achieve an unprecedentedly high performance for CO2RR. The optimized morphology, microrod array, exhibits a current density of ~10 mA cm−2 at −0.50 V vs. RHE with significantly increased Faraday efficiencies over a very broad potential range (0.35–0.7 V vs. RHE). Our complementary theoretical study reveals that the significantly enhanced electrocatalytic activity and selectivity at decreased overpotential can be attributed to the stepped/kinked surface and subsurface oxygen, which increase the binding energy of CO intermediates without altering hydrogen binding energy; and thus lower the overpotential for CO2RR and increase the selectivity of CO over hydrogen. Our work provides a cost-effective and scalable technique for making catalysts for energy-efficient conversion of CO2 to CO.